Anti-fatigue rubber composition, mixing method and application in preparing air spring

By optimizing the formulation and process, using rubber compositions including neoprene, carbon black and liquid butyl rubber, the problems of operational difficulties and fatigue resistance reduction caused by neoprene crystals are solved, and the problem of lower resistance is achieved. Heat generation and better fatigue resistance.

CN116656020BActive Publication Date: 2025-02-07ZHONGCE RUBBER GRP CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310680927.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2025-02-07
Estimated Expiration
2043-06-09

AI Technical Summary

Technical Problem

Neoprene is prone to crystallization at room temperature, which makes it difficult to operate the mixing process and calendering process. At the same time, the fatigue resistance and fatigue resistance of the air spring rubber combination made of neoprene with high crystallinity is reduced.

Method used

Using an anti-fatigue rubber composition including neoprene, carbon black, liquid butadiene rubber, anti-aging agent, microcrystalline wax, magnesium oxide, zinc oxide, sulfur, promoters and organic sulfur donors, by optimizing the formulation The mixing process reduces the energy storage modulus and Mooney viscosity of neoprene, and improves the processing performance and fatigue resistance of the rubber composition.

Benefits of technology

It achieves lower heat generation and better fatigue resistance, improves the mixing and calendering performance of air springs, and enhances its resistance to tortuous cracks and low temperature resistance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of preparation of air springs, and in particular to an anti-fatigue rubber composition, a mixing method and an application in the preparation of air springs. The chloroprene rubber used in the present invention has a lower storage modulus at 30°C. At the same time, liquid butadiene rubber is used to replace the environmentally friendly oil to reinforce the rubber composition, and the rubber composition has a lower Mooney viscosity (ML1+4)×100°C and a Young's modulus E' at ‑20°C. The lower the Mooney viscosity, the better the mixing performance and calendering performance of the rubber composition, and the better the anti-bending crack performance and low temperature resistance (characterized by the Young's modulus E' at ‑20°C) of the rubber composition. The present invention provides excellent mixing and calendering processes, and the air spring prepared using the rubber composition of the present invention has lower heat generation and better fatigue resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of air springs, and in particular to an anti-fatigue rubber composition, a mixing method and application in the preparation of air springs. Background Art

[0002] Since Ford adopted the McPherson suspension in 1950, it has been widely used by automobile manufacturers for automobile shock absorption due to its good responsiveness and handling. However, it has disadvantages such as the wheels being prone to automatic steering and poor stability when the car is driving on uneven roads.

[0003] In 1984, adjustable air suspension was used for automobile shock absorption. The air spring has ideal nonlinear elastic characteristics. After adding a height adjustment device, the height of the vehicle body does not change with the increase or decrease of the load. The spring stiffness can be designed to be lower, and the ride comfort is good. However, the air spring suspension has a complex structure and high manufacturing cost, and its application range is not as good as the McPherson suspension.

[0004] In recent years, new energy vehicles will be equipped with mild hybrid and plug-in hybrid. In the future, by 2050, pure electric and hydrogen energy will become the main energy sources for automobiles. The driving comfort of automobiles is increasingly concerned by consumers, and automotive engineers are paying more and more attention to air springs.

[0005] As air springs gradually replace mechanical shock absorbers for automobile shock absorption, the driving comfort of passenger cars has been improved. In the rubber composition of air springs, natural rubber, butadiene rubber, butyl rubber, chloroprene rubber, and nitrile rubber are widely used. Among them, chloroprene rubber is widely used in air springs due to its excellent physical properties, as well as oil resistance, heat resistance, and ozone resistance.

[0006] The Chinese invention patent applied by the applicant (publication number: CN115322463A, publication date: 2022-11-11) discloses a low-heating, anti-fatigue rubber composition for producing air springs, and its preparation method and application. The rubber composition is prepared by mixing the following raw materials based on 100 parts by weight of the rubber component: 100 parts of chloroprene rubber, 20-40 parts of carbon black, 5.0-30 parts of white carbon black, 1.0-5.0 parts of silane coupling agent, 5.0-20 parts of nano-sheet silicate, and 0-0.8 parts of organic sulfur donor. The patented gas spring has lower heat generation and better fatigue resistance.

[0007] Chinese invention patent (publication number: CN114672081A, publication date: 2022-06-28) A rubber composition for air springs, the rubber composition includes, by weight: 100 parts of chloroprene rubber, 25-50 parts of reinforcing agent; the reinforcing agent includes carbon black and white carbon black in a mass ratio of (20-35): (5-15). Through reasonable formula design, the rubber composition achieves excellent material mechanical properties, fatigue resistance and anti-aging properties in the case of thinner bladder skin, with a tensile strength of more than 23MPa and an elongation at break of more than 500%, so that the air spring has both comfort and various performances.

[0008] In all the above formulations, chloroprene rubber is used as the rubber system, but chloroprene rubber will crystallize at room temperature, which makes the mixing and calendering processes of chloroprene rubber difficult. In addition, the fatigue resistance of the rubber combination of the air spring made of high-crystallization chloroprene rubber is reduced. Summary of the invention

[0009] In order to solve the above technical problems, the purpose of the present invention is to provide an anti-fatigue rubber composition. The air spring prepared by using the rubber composition of the present invention has lower heat generation and better anti-fatigue performance.

[0010] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:

[0011] An anti-fatigue rubber composition is prepared by mixing the following raw materials based on 100 parts by weight of the rubber component:

[0012] Rubber 100 parts

[0013] Carbon black 45-60 parts

[0014] Liquid butadiene rubber 12-20 parts

[0015] Antiaging agent 3.0~11 parts

[0016] Microcrystalline wax 1.0~3.0 parts

[0017] 3.0~8.0 parts of magnesium oxide

[0018] Zinc oxide 8.0~12 parts

[0019] Sulfur 1.0-2.0 parts

[0020] Accelerator 0.5-2.0 parts

[0021] 0.1-0.8 parts of organic sulfur donor;

[0022] The rubber does not include liquid butadiene rubber, the amount of chloroprene rubber is 80 to 100 parts, the 30°C storage modulus of chloroprene rubber is ≤5 Mpa, and the Mn number average molecular weight of the liquid butadiene rubber is 5000-50000 g / mol; preferably, the Mn number average molecular weight of the liquid butadiene rubber is 8000-30000 g / mol.

[0023] Preferably, the composition is prepared by mixing the following raw materials based on 100 parts by weight of the rubber component:

[0024] Rubber 100 parts

[0025] Carbon black 50-55 parts

[0026] Liquid butadiene rubber 14-18 parts

[0027] Anti-aging agent 5.0~9.0 parts

[0028] Microcrystalline wax 1.0~3.0 parts

[0029] 3.0~8.0 parts of magnesium oxide

[0030] Zinc oxide 8.0~12 parts

[0031] Sulfur 1.0-2.0 parts

[0032] Accelerator 0.5-2.0 parts

[0033] 0.1 to 0.8 parts of organic sulfur donor.

[0034] Preferably, the storage modulus of the chloroprene rubber at 30°C is 0.5-2.0 Mpa, and most preferably, the storage modulus of the chloroprene rubber at 30°C is 1.0-1.5 Mpa.

[0035] Preferably, the rubber in the rubber composition further comprises one or two of natural rubber, butadiene rubber, styrene-butadiene rubber, butyl rubber, nitrile rubber and styrene-butadiene rubber, or a mixture of three or more thereof.

[0036] As a preferred embodiment, the carbon black iodine absorption value is 25 to 160 mg / g, and the CTAB adsorption specific surface area is 29 to 150 m 2 / g, preferably, the iodine absorption value of carbon black is 31-100 mg / g, and the CTAB adsorption specific surface area is 30-100 m 2 / g, further preferably, the carbon black has an iodine absorption value of 31 to 60 mg / g, and a CTAB adsorption specific surface area of ​​30 to 100 m 2 / g.

[0037] Preferably, the antioxidant is one or two of phenylnaphthylamine, substituted diphenylamine, and p-phenylenediamine, or a mixture of three or more thereof; the organic sulfur donor in the rubber composition is one or two of alkylphenol disulfides, or a mixture of three thereof, and the sulfur content in the organic sulfur donor is 20-40%.

[0038] Furthermore, the present invention also discloses a mixing method of the anti-fatigue rubber composition, which comprises the following steps:

[0039] The first step is mixing, mixing with an internal mixer, adding chloroprene rubber to the internal mixer and mixing for 30 to 100 seconds; then lifting the top bolt, adding all materials except zinc oxide, accelerator, sulfur, and organic sulfur donor, and then closing the feeding door, pressing the top bolt and keeping it for 400 to 1200 seconds, the rotor speed of the internal mixer is 5 to 30 rpm, and the rubber discharge temperature is 90 to 105°C;

[0040] The second step is mixing, and mixing is performed using an internal mixer. The mixture obtained in the first step and the remaining raw materials are all added to the internal mixer, the feeding door is closed, the top bolt is pressed and maintained for 200 to 800 seconds, the rotor speed of the internal mixer is 5 to 30 revolutions / min, and the rubber discharge temperature is 85 to 100° C.; and the final rubber composition is obtained.

[0041] Preferably, in the first step of mixing, the mixing time of adding chloroprene rubber to the internal mixer is 40 to 80 seconds, the time of pressing the top bolt is 600 to 1000 seconds, and the rotor speed of the internal mixer is 10 to 20 rpm; more preferably, the mixing time of adding chloroprene rubber to the internal mixer is 50 to 70 seconds, the time of pressing the top bolt is 700 to 900 seconds, and the rotor speed of the internal mixer is 10 to 15 rpm;

[0042] In the second step of mixing, the top bolt is pressed and maintained for 300 to 600 seconds, the rotor speed of the internal mixer is 10 to 20 rpm, and the debinding temperature is 90 to 100° C.; more preferably, the top bolt is pressed and maintained for 400 to 550 seconds, the rotor speed of the internal mixer is 10 to 15 rpm, and the debinding temperature is 90 to 95° C.

[0043] Furthermore, the present invention also discloses the use of the anti-fatigue rubber composition in the preparation of vehicle air springs.

[0044] Furthermore, the present invention also discloses a vehicle air spring, which is prepared by vulcanizing the rubber composition.

[0045] Due to the adoption of the above technical solution, the chloroprene rubber used in the present invention has a lower storage modulus at 30°C. At the same time, liquid butadiene rubber is used to replace the environmentally friendly oil to reinforce the rubber composition, and the rubber composition has a lower Mooney viscosity (ML1+4)×100°C and -20°C Young's modulus E'. The lower the Mooney viscosity, the better the mixing performance and calendering performance of the rubber composition, and the better the flexural crack resistance and low temperature resistance (characterized by -20°C Young's modulus E') of the rubber composition. The present invention provides excellent mixing and calendering processes, and the air spring prepared using the rubber composition of the present invention has lower heat generation and better fatigue resistance. DETAILED DESCRIPTION

[0046] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Comparative Examples and Examples are shown in Table 1; the sources of the raw materials used are as follows:

[0048] 1 Neoprene A, CR90, made by Japan Electric Chemical Co., Ltd.

[0049] 2 Neoprene E, DCR40A, Nippon Denki Chemical Products;

[0050] 3 Carbon black N660, produced by Hangzhou Zhongce Qingquan Industrial Co., Ltd.

[0051] 4 Liquid butadiene rubber LBR305, Mn number average molecular weight 26000, Japan Kuraray Chemical Co., Ltd.

[0052] 5 Rubber oil, V700, Ningbo Hansheng Chemical Co., Ltd.

[0053] 6 Antioxidant 6PPD, Shandong Shengao Chemical Technology Co., Ltd.

[0054] 7 Antioxidant DTPD, Yixing Jujinxin Technology Co., Ltd.

[0055] 8. Organic sulfur donor, TB710, sulfur 27.4%, Shandong Yanggu Huatai Chemical Co., Ltd.

[0056] 9. Other raw materials are industrial products sold in the market.

[0057] The mixing method of the rubber composition described in the comparative examples and examples in Table 1 comprises the following steps:

[0058] The first step is mixing. The chloroprene rubber (and natural rubber) is added to the internal mixer and mixed for 50 to 70 seconds. Then, the top bolt is raised and all materials except zinc oxide, accelerator, sulfur, and organic sulfur donor (if any) are added. Then, the feeding door is closed and the top bolt is pressed and kept for 700 to 900 seconds. The rotor speed of the internal mixer is 10 to 15 rpm and the discharge temperature is 90 to 105°C.

[0059] The second step is mixing, and mixing is performed using an internal mixer. The mixture obtained in the first step and the remaining raw materials are all added to the internal mixer, the feeding door is closed, the top bolt is pressed and maintained for 400 to 550 seconds, the rotor speed of the internal mixer is 10 to 15 revolutions per minute, and the discharge temperature is 90 to 95° C.; the final rubber composition is obtained.

[0060] The calendering method of the rubber composition described in the comparative examples and examples in Table 1 comprises the following steps:

[0061] 1) Extrusion through extruder 1 and extruder 2, the cooling water of extruder 1 and extruder 2 is 20-60℃, the screw speed is 3-8 rpm; the temperature of the rubber compound extruded by the extruder is 50-95℃;

[0062] 2) After extrusion, the rubber material is rolled by a four-roll calender. The temperature of the rubber material on the four-roll calender is 75-100℃, and the cooling water of the four-roll calender is 30-60℃;

[0063] 3) After cooling by the cooling roller, the film is rolled up and taken up. The film taking-up speed is 3-12m / min.

[0064] Methods used to evaluate performance

[0065] The performance tests in Tables 1 and 2 are carried out according to the corresponding national standards.

[0066] Neoprene crystallinity test

[0067] The crystallinity of chloroprene rubber is characterized by the storage modulus at 30°C. The smaller the storage modulus at 30°C, the smaller the crystallinity of chloroprene rubber, the better the processing performance and the better the fatigue resistance.

[0068] Test instrument: RSA-G2, TA Instruments, USA

[0069] Test method: -80~100℃ temperature scan, heating rate 5℃ / min, frequency 1.59 Hz, strain 2%;

[0070] Test data: 30℃ storage modulus.

[0071] Processing performance test

[0072] The processing properties of the rubber composition are characterized by the Mooney viscosity. The lower the Mooney viscosity, the better the mixing and calendering properties of the rubber composition.

[0073] Test instrument: Norja Mooney Viscometer MVS3L, a product of Shanghai Norja Instrument Co., Ltd.

[0074] Test data: Mooney viscosity is ML (1+4) × 100℃.

[0075] Low temperature resistance

[0076] The low temperature resistance of the rubber composition is characterized by the Young's modulus E' at -20℃. The smaller the -20℃ E', the better the low temperature resistance.

[0077] Test instrument: VR-7120 dynamic thermomechanical analysis manufactured by UESHIMA, Japan;

[0078] The test conditions are -50~80℃, frequency 20Hz, dynamic strain 0.25%;

[0079] Test data: -20℃E'.

[0080] Flexural crack resistance index

[0081] The larger the anti-bending crack index is, the better the fatigue resistance is, see formula (1)

[0082] Anti-flexion crack index = flexion crack of embodiment / flexion crack of comparative example 1 formula (II).

[0083] Table 1

[0084] Storage modulus at 30℃MPa Neoprene A 26.61 Neoprene E 1.15

[0085] Table 2

[0086] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Example 1 Example 2 Example 3 Example 4 Neoprene A 100.0 100.0 Neoprene E 100.0 100.0 100.0 100.0 100.0 90.0 Natural rubber 10.0 Liquid butadiene rubber 5.0 15.0 10.0 15.0 20.0 15.0 Environmentally friendly oil 15.0 15.0 10.0 5.0 Carbon Black 51.0 51.0 51.0 51.0 51.0 51.0 51.0 51.0 Stearic acid 2.0 2.0 2.0 2.0 2.0 2.0 2.0 2.0 Antioxidant 6PPD 4.0 4.0 4.0 4.0 4.0 4.0 4.0 4.0 Antioxidant DTPD 3.0 3.0 3.0 3.0 3.0 3.0 3.0 3.0 Microcrystalline wax SL-10345 2.0 2.0 2.0 2.0 2.0 2.0 2.0 2.0 Magnesium Oxide 5.0 5.0 5.0 5.0 5.0 5.0 5.0 5.0 Indirect zinc oxide 10.0 10.0 10.0 10.0 10.0 10.0 10.0 10.0 Accelerator CZ 1.0 1.0 1.0 1.0 1.0 1.0 1.0 1.0 10% oil-filled sulfur 1.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 TB710 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Mooney viscosity (ML1+4) × 100℃ 77.8 68.3 63.5 72.1 57.0 51.2 45.7 44.1 Low temperature performance-20℃E' / MPa 636.4 134.4 119.5 280 101.8 80.5 56.3 61.5 Tortuosity index 100 1188 1573 783 2350 2518 2730 1834

[0087] The above is a description of the embodiments of the present invention. Through the above description of the disclosed embodiments, professionals and technicians in the field can implement or use the present invention. Various modifications to these embodiments will be apparent to professionals and technicians in the field. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to these embodiments shown in this article, but will conform to the widest range consistent with the principles and novelties disclosed herein.

Claims

1. An anti-fatigue rubber composition, characterized in that: The composition is prepared by mixing the following raw materials based on 100 parts by weight of the rubber component: Rubber 100 parts Carbon black 45-60 parts Liquid butadiene rubber 10-20 parts Rubber oil 0~8 parts Antiaging agent 3.0~11 parts Microcrystalline wax 1.0~3.0 parts 3.0-8.0 parts of magnesium oxide Zinc oxide 8.0~12 parts Sulfur 1.0-2.0 parts Accelerator 0.5-2.0 parts 0.1-0.8 parts of organic sulfur donor; The rubber includes chloroprene rubber, but does not include liquid butadiene rubber. The amount of chloroprene rubber used is 80 to 100 parts. The 30°C storage modulus of the chloroprene rubber is ≤5 Mpa, and the Mn number average molecular weight of the liquid butadiene rubber is 5000-50000 g / mol.

2. The anti-fatigue rubber composition according to claim 1, characterized in that: The composition is prepared by mixing the following raw materials based on 100 parts by weight of the rubber component: Rubber 100 parts Carbon black 50-55 parts Liquid butadiene rubber 14-18 parts Rubber oil 0~5 parts Anti-aging agent 5.0~9.0 parts Microcrystalline wax 1.0~3.0 parts 3.0-8.0 parts of magnesium oxide Zinc oxide 8.0~12 parts Sulfur 1.0-2.0 parts Accelerator 0.5-2.0 parts 0.1 to 0.8 parts of organic sulfur donor.

3. An anti-fatigue rubber composition according to claim 1 or 2, characterized in that: The Mn number average molecular weight of liquid butadiene rubber is 8000-30000 g / mol.

4. An anti-fatigue rubber composition according to claim 1 or 2, characterized in that: The storage modulus of chloroprene rubber at 30°C is 0.5-2.0 Mpa.

5. An anti-fatigue rubber composition according to claim 1 or 2, characterized in that: The storage modulus of chloroprene rubber at 30°C is 1.0-1.5 Mpa.

6. An anti-fatigue rubber composition according to claim 1 or 2, characterized in that: The rubber in the rubber composition also includes one or two of natural rubber, butadiene rubber, styrene-butadiene rubber, butyl rubber, nitrile rubber and styrene-butadiene rubber, or a mixture of three or more of them.

7. An anti-fatigue rubber composition according to claim 1 or 2, characterized in that: The carbon black iodine absorption value is 25-160 mg / g, and the CTAB adsorption specific surface area is 29-150 m 2 / g.

8. An anti-fatigue rubber composition according to claim 1 or 2, characterized in that: The iodine absorption value of carbon black is 31-100 mg / g, and the CTAB adsorption specific surface area is 30-100 m 2 / g.

9. An anti-fatigue rubber composition according to claim 1 or 2, characterized in that: The iodine absorption value of carbon black is 31-60 mg / g, and the CTAB adsorption specific surface area is 30-100 m 2 / g.

10. An anti-fatigue rubber composition according to claim 1 or 2, characterized in that: The antioxidant is one of phenylnaphthylamine, substituted diphenylamine, and p-phenylenediamine, or two of them, or a mixture of three or more thereof; the organic sulfur donor in the rubber composition is one of alkylphenol disulfide, or a mixture of three of them, and the sulfur content in the organic sulfur donor is 20-40%.

11. A mixing method for an anti-fatigue rubber composition according to any one of claims 1 to 10, characterized in that: The method comprises the following steps: The first step is mixing, mixing with an internal mixer, adding chloroprene rubber to the internal mixer and mixing for 30 to 100 seconds; then lifting the top bolt, adding all materials except zinc oxide, accelerator, sulfur, and organic sulfur donor, and then closing the feeding door, pressing the top bolt and keeping it for 400 to 1200 seconds, the rotor speed of the internal mixer is 5 to 30 rpm, and the rubber discharge temperature is 90 to 105°C; The second step is mixing, and mixing is performed using an internal mixer. The mixture obtained in the first step and the remaining raw materials are all added to the internal mixer, the feeding door is closed, the top bolt is pressed and maintained for 200 to 800 seconds, the rotor speed of the internal mixer is 5 to 30 revolutions / min, and the rubber discharge temperature is 85 to 100° C.; and the final rubber composition is obtained.

12. The method according to claim 11, characterized in that The method comprises the following steps: The first step is mixing, the chloroprene rubber is added to the internal mixer for a mixing time of 40 to 80 seconds, the top bolt is pressed and held for 600 to 1000 seconds, and the rotor speed of the internal mixer is 10 to 20 revolutions per minute; In the second step of mixing, the top bolt is pressed and maintained for 300 to 600 seconds, the rotor speed of the internal mixer is 10 to 20 revolutions per minute, and the discharge temperature is 90 to 100°C.

13. The method according to claim 12, characterized in that In the first step of mixing, the chloroprene rubber is added to the internal mixer for a mixing time of 50 to 70 seconds, the top bolt is pressed and maintained for 700 to 900 seconds, and the rotor speed of the internal mixer is 10 to 15 revolutions per minute.

14. The method according to claim 12, characterized in that In the second step of mixing, the top bolt is pressed and maintained for 400 to 550 seconds, the rotor speed of the internal mixer is 10 to 15 rpm, and the discharge temperature is 90 to 95°C.

15. A calendering method for an anti-fatigue rubber composition according to any one of claims 1 to 10, the method comprising the following steps: 1) Extrusion through extruder 1 and extruder 2, the cooling water of extruder 1 and extruder 2 is ≤70℃, the screw speed is ≤10 turns; the temperature of the rubber compound extruded by the extruder is ≤100℃; 2) After extrusion, the rubber material is rolled by a four-roll calender. The temperature of the rubber material on the four-roll calender is ≤105℃, and the cooling water of the four-roll calender is ≤80℃; 3) After cooling by the cooling roller, the film is rolled up and taken up, and the film taking-up speed is ≤15m / min.

16. The method according to claim 15, characterized in that In step 1), the cooling water of extruder 1 and extruder 2 is 20-60°C, the screw speed is 3-8 rpm, and the temperature of the rubber compound extruded by the extruder is 50-95°C.

17. The method according to claim 15, characterized in that Step 2) The temperature of the rubber compound on the four calendering rollers is 75-100°C, and the cooling water of the four calendering rollers is 30-60°C.

18. The method according to claim 15, characterized in that In step 3), the film winding speed is 3-12 m / min.

19. A vehicle air spring, characterized in that: The air spring is prepared by vulcanizing the rubber composition described in any one of claims 1 to 10.

Citation Information

Patent Citations

  • Rubber composition for air spring and preparation method thereof

    CN114672081A

  • Low-heat-generation and anti-fatigue rubber composition as well as preparation method and application thereof

    CN115322463A

  • Production of rubber

    JP1994128420A